Indonesia Pengaruh Costumer Relationship Dan Promosi Penjualan Terhadap Loyalitas Pelanggan Di PT Valco Indonesiatec : Pengaruh Costumer Relationship Dan Promosi Penjualan Terhadap Loyalitas Pelanggan Di PT Valco Indonesiatec - Ridarti, Hidayah Fitri Ridarti; Wangdra, Yvonne (SCIENTIA JOURNAL, 2023)
In the midst of intense competition, one of the keys to maintaining and keeping up with the company's future is client or customer loyalty. The purpose of this research is to determine the effect of customer relationships and sales promotions on customer loyalty at PT Valco Indosiatec. This study applies a quantitative method by determining a sample of 101 respondents at PT Valco Indosiatec by applying a saturated sample. Questionnaires are used as a technique in collecting data. Data analysis in this study used the SmartPLS 3.0 program. Hypothesis testing with the PLS approach is carried out in two stages, namely testing the outer model and the inner model. The outer model test is carried out to prove the validity and reliability of all indicators for each variable. The inner model test is carried out to test the influence between variables according to the hypotheses previously set. The results showed: customer relationship has an effect on PT Valco Indosiatec's sales promotion, sales promotion has an effect on PT Valco Indosiatec's customer loyalty, customer relationship has an effect on PT Valco Indosiatec's customer loyalty